DILEMA PEMBENTUKAN CADANGAN AKTIVA PRODUKTIVE BANK : SEBUAH STUDI HASIL MERGER PADA BANK PERKREDITAN RAKYAT BKK KABUPATEN REMBANG - Mokhamat Ansori (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2007)
Abstract Financial minister (MENKEU), in February, 6, 1995 has published: Surat Keputusan No. 080/KMK.04/1995 about allowance for doubtful account (Cadangan Penghapusan piutang). Based on it, allowance for productive asset or Cadangan Aktiva Produktif (CAP) which can agree as cost in fiscal finance report, maximum is 3% from average of first saldo and final asset.CAP is allowance for anticipated probability unpaid the allocation funds that have done by bank into productive asset (Aktiva Produktif –AP). This article,in detail, explained urgency of CAP in the bank. Specially, it is Bank Perkreditan Rakyat (BPR) that has merger in Kabupaten Rembang. This article’s author has ever as employee in this bank. It is dilemma, if it must to prepare CAP. Cause BPR, generally its Non Performing Loan, is above 5%.